A Revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 1 (Introductory material, key to species-groups and keys to species of the thoracica, pusilla, formosa, propinqua & gloriosa species-groups) - Levey, Brian (Zootaxa, 2012)
This is the first part of a revision of the Australian members of the genus Melobasis Laporte & Gory 1837. A synopsis ofthe biogeography, biology and relationships of Melobasis is given. A key to species-groups, and keys to the species ofthe formosa, gloriosa, thoracica, propinqua and pusilla species-groups are provided, together with descriptions andillustrations of all the species of these groups.26 new species and subspecies are described: M. acutula sp. n., M. amoena sp. n., M. angusta sp. n., M. brevis sp.n., M. brittoni sp. n., M. burnsi sp. n., M. dividua sp. n., M. duplexicolor sp. n., M. eximia sp. n., M. flavoaenea sp. n.,M. flexa sp. n., M. goerlingi sp. n., M. hanloni sp. n., M. janae sp. n., M. kanguluorum sp. n., M. knowlesi sp. n., M.nudipectus sp. n., M. paucipunctata sp. n., M. powelli sp. n., M. propinqua depressa ssp. n.., M. purpurilata sp. n., M.rectipilosa sp. n., M. regalis carnabyorum ssp. n, M. similis sp. n., M. simulata sp. n., M. specularis sp. n.The following new synonymies are proposed: Briseis Saunders 1871, Diceropygus Deyrolle 1864 and ParamelobasisThéry 1923 are synonymised with Melobasis.Melobasis bimetallica Carter 1923 and M. cuprina Kerremans 1898 are synonymised with M. g. gloriosa (Laporte &Gory 1837); M. goryi Saunders 1871 and M. metallifera Saunders 1868 are synonymised M. cuprifera (Laporte & Gory1837); M. nitidiventris Kerremens 1898 is synonymised with M. thoracica Blackburn 1887; M. subconica Carter 1923 issynonymised with M. uniformis Carter 1923; M. terminata Kerremans 1898 is synonymised with M. inflammabilisThomson 1879. The following changes of status are proposed: M. cruentata Thomson 1879 is made a subspecies of M.gloriosa (Laporte & Gory 1837); M. cuprifera (Laporte & Gory 1837) is removed from synonymy with M. propinqua(Laporte & Gory 1837); M. inflammabilis Thomson 1879 is removed from synonymy with M. vittata Blackburn 1887; M. verna (Hope 1846) is raised to a subspecies of M. propinqua (Laporte & Gory 1837);